Finding the root of the problem

Algebra Level 4

40 x 1 160 x 4 200 x 5 + 320 x 8 = 6 x 2 27 x \dfrac{40}{x-1} - \dfrac{160}{x-4} - \dfrac{200}{x-5} + \dfrac{320}{x-8} = 6x^2 - 27x

The equation given above has both real as well as complex roots. Considering only the real roots, if two of its roots are α \alpha and β \beta respectively such that log α ( 2 β ) \log_{\alpha} \left(2\beta\right) is defined and is an integer, then evaluate its value.


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Nov 26, 2016

40 x 1 160 x 4 200 x 5 + 320 x 8 = 6 x 2 27 x 40 x 1 200 x 5 + 320 x 8 160 x 4 = 3 x ( 2 x 9 ) 40 x 200 200 x + 200 ( x 1 ) ( x 5 ) + 320 x 1280 160 x + 1280 ( x 8 ) ( x 4 ) = 3 x ( 2 x 9 ) 160 x ( x 1 ) ( x 5 ) + 160 x ( x 8 ) ( x 4 ) = 3 x ( 2 x 9 ) 160 x ( x 2 6 x + 5 x 2 + 12 x 32 ) ( x 1 ) ( x 4 ) ( x 5 ) ( x 8 ) = 3 x ( 2 x 9 ) 160 x ( 6 x 27 ) ( x 1 ) ( x 4 ) ( x 5 ) ( x 8 ) = 3 x ( 2 x 9 ) 3 x ( 2 x 9 ) ( 160 ( x 1 ) ( x 4 ) ( x 5 ) ( x 8 ) 1 ) = 0 \begin{aligned} \frac {40}{x-1} - \frac {160}{x-4} - \frac {200}{x-5} + \frac {320}{x-8} & = 6x^2 - 27x \\ \frac {40}{x-1} - \frac {200}{x-5} + \frac {320}{x-8} - \frac {160}{x-4} & = 3x(2x - 9) \\ \frac {40x-200 - 200x+200}{(x-1)(x-5)} + \frac {320x-1280 - 160x+1280}{(x-8)(x-4)} & = 3x(2x - 9) \\ - \frac {160x}{(x-1)(x-5)} + \frac {160x}{(x-8)(x-4)} & = 3x(2x - 9) \\ \frac {160x(x^2-6x+5-x^2+12x-32)}{(x-1)(x-4)(x-5)(x-8)} & = 3x(2x - 9) \\ \frac {160x(6x-27)}{(x-1)(x-4)(x-5)(x-8)} & = 3x(2x - 9) \\ 3x(2x-9) \left(\frac {160}{(x-1)(x-4)(x-5)(x-8)} -1 \right) & = 0 \end{aligned}

Therefore, there are three real roots to the equation x = 0 x=0 , x = 9 2 x = \dfrac 92 and:

160 ( x 1 ) ( x 4 ) ( x 5 ) ( x 8 ) = 1 ( x 1 ) ( x 4 ) ( x 5 ) ( x 8 ) = 160 \begin{aligned} \frac {160}{(x-1)(x-4)(x-5)(x-8)} & = 1 \\ \implies (x-1)(x-4)(x-5)(x-8) & = 160 \end{aligned}

We note that when x = 0 x=0 , ( x 1 ) ( x 4 ) ( x 5 ) ( x 8 ) = ( 1 ) ( 4 ) ( 5 ) ( 8 ) = 160 (x-1)(x-4)(x-5)(x-8) = (-1)(-4)(-5)(-8) = 160 , so is when x = 9 x = 9 , ( 9 1 ) ( 9 4 ) ( 9 5 ) ( 9 8 ) = ( 8 ) ( 5 ) ( 4 ) ( 1 ) = 160 (9-1)(9-4)(9-5)(9-8) = (8)(5)(4)(1) = 160 . Since x = 0 x=0 is already a root the third root is x = 9 x=9 .

Putting α = 9 \alpha = 9 and β = 9 2 \beta = \dfrac 92 , then log α ( 2 β ) = log 9 9 = 1 \log_\alpha (2\beta) = \log_9 9 = \boxed{1} .

Again a great solution sir! :) +1

Tapas Mazumdar - 4 years, 6 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...